(untitled) (Research, Society and Development, 2022)
This study aimed to evaluate the carcass yield, to determine the chemical composition of the filet and to evaluate the physical-mechanical resistance of the Nile tilapia leather produced in ponds and cages. The results obtained for body characteristics, yields, morphometric relations, filet chemical composition and physical-mechanical tests of the tilapia leather from both farming systems were submitted to variance analysis (ANOVA), and when statistical differences were observed, Tukey’s test was applied at 5% significance level, using the Statistica 7.1 software. Significant differences were observed for the mean values of body characteristics between the two types of farming for total and standard length, total weight, fins and fillet weight. As for morphometric relationships, chemical composition of fillets and leather strength, no significant differences were observed. It is concluded that the production system influences some carcass characteristics, without influencing the body yield, morphometric relations, meat composition and physical-mechanical tests of the leather. The resistance, traction and tearing tests of the tilapia leather indicate the possibility of its use in the textile industry.